2007
DOI: 10.1038/sj.onc.1210572
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Knockdown of astrocyte-elevated gene-1 inhibits prostate cancer progression through upregulation of FOXO3a activity

Abstract: Astrocyte-elevated gene-1 (AEG-1) has been reported to be upregulated in several malignancies and play a critical role in Ha-ras-mediated oncogenesis through the phosphatidylinositol 3-kinase/AKT signaling pathway. However, the role of AEG-1 in prostate cancer (PC) has never been reported. We now show that AEG-1 is overexpressed in clinical PC tissue samples and cultured PC cells compared to benign prostatic hyperplasia tissue samples and normal prostate epithelial cells. Interestingly, AEG-1 knockdown induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
153
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 28 publications
8
153
1
Order By: Relevance
“…The results showed that transcription factors able to bind directly to the eIF4E promoter included NFκB, C/EBPα and β, AP‐1, SP‐1, RXRβ and Oct‐1. Previous studies showed that by activating PI3K/Akt signalling, AEG‐1 activated the transcription factors FoxO1, FoxO3a, NFκB and AP‐1 32, 51, 52. Moreover, AEG‐1 directly interacted with p65‐NFκB, SND1 and PLZF to regulate gene transcription 50, 53, 54.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that transcription factors able to bind directly to the eIF4E promoter included NFκB, C/EBPα and β, AP‐1, SP‐1, RXRβ and Oct‐1. Previous studies showed that by activating PI3K/Akt signalling, AEG‐1 activated the transcription factors FoxO1, FoxO3a, NFκB and AP‐1 32, 51, 52. Moreover, AEG‐1 directly interacted with p65‐NFκB, SND1 and PLZF to regulate gene transcription 50, 53, 54.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative PCR was conducted using FastStart Universal SYBR Green PCR Master mix (4913914001) (Rox; 11929100) from Roche (Indianapolis, IN, USA), according to the manufacturer's instructions. The forward (F) and reverse (R) primers were synthesized by Invitrogen as follows: AEG‐1, F: 5′‐ACGACCTGGCCTTGCTGAAGAATCT‐3′ and R: 5′‐CGGTTGTAAGTTGCTCGGTGGTAA‐3′; eIF4E, F: 5′‐CCTACAGAACAGATGGGCACTC‐3′ and R: 5′‐GCCCAAAAGTCTTCAACAGTATCA‐3′; GAPDH, F, 5′‐ATGGGGAAGGTGAAGGTCG‐3′ and R, 5′‐GGGGTCATTGATGGCAACAATA‐3′ 32, 33. All measurements were performed in triplicate and measured with the ABI Prism 7300 sequence detection system (Applied Biosystems, Foster City, CA, USA), as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the abundance of MTDH phenotypes, a consensus understanding of its underlying molecular mechanisms has not yet been reached. MTDH has been shown to influence several oncogenic signaling pathways and transcription factors, such as Ha-Ras (15), PI3K/AKT (13), ERK, Wnt/␤-catenin (8), NF-B (16), c-Myc (15), and FOXO1/FOXO3a (17,18). However, MTDH regulation of signaling pathways appears to be context-dependent with affected pathways varying by tumor type and cell line (19,20).…”
mentioning
confidence: 99%
“…Overexpression of AEG-1 also augmented the anchorage-independent growth of HeLa cells and human glioma cell lines and increased their migration and invasion properties (14,15). Conversely, inhibition of AEG-1 by siRNA significantly inhibited migration and invasion of malignant glioma cells and prostate cancer cells and in vivo lung metastasis of breast cancer cells (16)(17)(18)(19). In PHFA, FM516-SV, and cloned rat embryo fibroblasts (CREF), AEG-1 protects from serum starvation-induced apoptosis by activating the PI3K/Akt signaling pathway indicating, but not definitively proving, that AEG-1 might function as an oncogene (20).…”
mentioning
confidence: 99%